Smart Safety Helmet in Coal Mining Using Arduino (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Coal mining industry is very important for the nation’s economy. The Need for coal is high nowadays. Coal plays a vital role in generation of electricity, steel and cement production. Nowadays thousands of miners lose them from mining accidents each year mainly from underground coal mining. Coal mining is considered much more dangerous than hard rock mining. Most of the deaths occur in developing countries such as India, Argentina, Armenia and rural parts of developed countries. Keeping this in mind we design a helmet for the safety of mine workers. In our system we are detecting dangerous gas such as methane and carbon monoxide, collision and temperature and humidity in underground area and nRF24L01 are used for transferring collected values. To save mine workers life in underground mining smart helmets have been developed. The sensors are connected to a microcontroller which is place in underground coal mining areas which detects the value and sends through RF transmitter to receiver which is placed in the helmet. The helmet also consists of microcontroller, buzzer and LCD display. The dangerous gases, collision and temperature parameters are detected using gas sensors and temperature sensor and if the collected values of sensors are compared with limit, if its greater than the buzzer in the helmet gives alert signal as well as turns on the LCD and shows the status. The status of the gas sensor, collision sensor and humidity sensor values are transmitting to the mine workers by the RF transmitter to the RF receiver which is located in the helmet. By transmitting that detected information from the sensor to the miners’ helmet we can give warning so they can take safety precautions.